TIME DRIVEN ACTIVITY-BASED COSTIN IN HEALTH SECTOR - Mediaty; Asri Usman; Ririn Akhriani; Elwiyani Army (ZILLZELL MEDIA PRIMA, 2023)
This study aims to determine the use of TDABC in formulating health costs and the effect of cost management using TDABC on the health sector. The results of the study are that cost determination with the ABC method is difficult to implement by many organizations because of the high costs that must be incurred for interviews and surveys, the use of subjective and expensive time allocations to validate, and the difficulty of maintaining and updating models. While TDABC only requires estimation of two parameters. Daycoaches can account for complex activities and processes and provide more accurate cost information using time constraints and cost drivers. Therefore, processes with high cost and high variability can be identified and improved. The study concluded that TDABC can provide an accurate assessment of resource consumption and identify potential areas to improve efficiency. TDABC can be used as a strategic decision-making tool regarding the design of more effective treatment lines and thus contribute to cost measurement. The research method used is systematic literature review using PRISMA approach.